Evaluation of Critical Thinking Ability Through The Development of Contextual Physics Teaching Materials Assisted by Socratic Question - Nurita Apridiana Lestari; Gunawan Hadi Winarto (Phenomenon : Jurnal Pendidikan MIPA, 2022)
This research is one of the stages of developing contextual teaching materials assisted by Socratic questions in physics learning with the primary material of Thermodynamics. The purpose of the evaluation stage is to determine the effectiveness of applying contextual teaching materials assisted by Socratic questions on students' critical thinking skills. The development research was carried out using the ADDIE method, which consisted of the following stages: Analysis, Design, Development, Implementation, Evaluation. The implementation of teaching materials using Socratic questions with Thermodynamics material was carried out for four meetings which 64 students attended. The parameters measured in this evaluation stage are the product quality of teaching materials and students' critical thinking skills. The results showed that (1) the process of developing contextual physics teaching materials assisted by Socratic Questions had met the product quality criteria, which included validity, practicality, and effectiveness (2) there was a significant difference between students' critical thinking skills in physics using Socratic-assisted contextual teaching materials—question without product application. In addition, it was found that the profile of students' critical thinking skills in physics learning using contextual physics teaching materials products Socratic questions was higher than in learning that did not use contextual physics teaching materials assisted by Socratic questions (with critical thinking indicators consisting of giving arguments, induction, evaluating, and make decisions).